The contents of unnamed contracts - Tatar, Olga; Mihalache, Iurie (Editura USM, 2024)
Any construction, whether named or unnamed, is a new model, consisting of various kinds of conditions and features that reflect the interests of society and the state as a whole. The peculiarity of the new contractual structure in the form of an unnamed contract is the presence of a definition of the subject of the legal relationship, along with the object, the subject, the essential and distinctive conditions of this contract, the rights and obligations of the parties, the procedure for concluding, changing and terminating the contract, the responsibility of the parties under the contract. At the same time, the contract is considered concluded when the parties have agreed on all the terms of the contract, without going beyond the generally known legal procedure.

Orice construcție, denumită sau nenumită, este un model nou, constând din diferite tipuri de condiții și trăsături care reflectă interesele societății și ale statului în ansamblu. Particularitatea noii structuri contractuale sub forma unui contract nenumit este prezenta unei definitii a subiectului raportului juridic, alaturi de obiectul, subiectul, conditiile esentiale si distinctive ale acestui contract, drepturile si obligatiile părțile, procedura de încheiere, modificare și încetare a contractului, responsabilitatea părților în temeiul contractului. Totodată, contractul se consideră încheiat atunci când părțile au convenit asupra tuturor termenilor contractului, fără a depăși procedura legală general cunoscută.
Keywords: unnamed contract; specifics of the contract; subjects and objects of the contract; content of the contract; distinctive features of the contract; contract nenumit; specificul contractului; obiectele și obiectele contractului; caracteristicile distinctive ale contractului